EXPLORING THE UNIQUENESS AND DISTINCTIVENESS OF TIMOR LESTE CULTURE THROUGH STORY AND NARRATIVE EXPLORATION: AN ANALYSIS OF FACTORS INFLUENCING TOURISM DESTINATION PROMOTION - Rezki Akbar Norrahman (PT. Banjarese Pacific Indonesia, 2024)
culture through the exploration of stories and narratives, as well as analyze the factors that influence the promotion of tourism destinations in this region. The research method used is qualitative with the main source of data coming from literature studies, mainly focusing on folklore, historical narratives, and Timor Leste's cultural richness. The introduction of the research covered the context of tourism in Timor Leste, highlighting the challenges in promoting tourism destinations and the problems faced. An in-depth literature search was then conducted to formulate the research problems, namely constraints in tourism promotion and the role of stories and narratives in the context of destination promotion. In the exploration of cultural uniqueness, the findings show that local mythology, oral traditions and community values play an important role in shaping Timor Leste's cultural identity. The analysis of factors influencing destination promotion involved an evaluation of marketing, tourism infrastructure, media, technology and sustainability aspects. The results of this study provide an in-depth insight into Timor Leste's local wisdom and tourism potential. The findings are expected to serve as a basis for the development of more effective promotional strategies, integrating cultural uniqueness in stories and narratives as a foundation for increasing the attractiveness of this tourism destination in the eyes of global travelers